2020
DOI: 10.1080/15427528.2020.1803169
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among commercial arabica coffee (Coffea arabica L.) varieties in Ethiopia using simple sequence repeat markers

Abstract: Ethiopia is the center of origin and genetic diversity of arabica coffee. Forty-two commercial arabica coffee varieties were developed by Jimma Agricultural Research Center (JARC) of Ethiopian Institute of Agricultural Research (EIAR) and released for production under diverse agro-ecologies of the country. Information on the level of genetic diversity among these varieties is scarce. Out of the 42 varieties, the genetic diversity of 40 widely cultivated commercial varieties was assessed using 14 simple sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 38 publications
5
18
0
Order By: Relevance
“…Further, Silvestrini et al [ 62 ] reported that even if coffee accessions had originated in the same localities, there was a possibility of separating genetically by the domestication process due to human selection activity. The finding also supports earlier reports that suggested southwest Ethiopia as the center of origin and diversity of C. arabica L. [ 8 , 12 , 17 , 63 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Further, Silvestrini et al [ 62 ] reported that even if coffee accessions had originated in the same localities, there was a possibility of separating genetically by the domestication process due to human selection activity. The finding also supports earlier reports that suggested southwest Ethiopia as the center of origin and diversity of C. arabica L. [ 8 , 12 , 17 , 63 ].…”
Section: Discussionsupporting
confidence: 92%
“…Coffea arabica L. is the only coffee species cultivated and exported from Ethiopia [ 12 ]. It is the major foreign exchange earner contributing to a quarter of the country’s export earnings [ 13 ] and serves as a means of livelihood and employment for an estimated 15 million people [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Former studies (Anthony et al, 2002;da Silva et al, 2019;Benti et al, 2020) had proven the efficiency of SSR markers to study the genetic diversity of Arabica. In our study, we confirm that the reduced set of SSR markers established by Pruvot-Woehl et al (2020) are efficient to describe a new genetic group in Yemen (Montagnon et al, 2021) is again efficient to describe a new genetic group in this species: the South Sudan group.…”
Section: Genetic Diversity Of South Sudan Arabicamentioning
confidence: 99%
“…arabica is mainly native to the highlands of southwestern Ethiopia, South Sudan (Boma plateau), and north Kenya (Mount Marsabi). C. arabica cultivars grown all around the world are derived from either 'Typica' or 'Bourbon' genetic base [17]. Studies report wide agronomic diversity of Arabica coffee accessions collected in these regions of Ethiopia regarding leaf size, height, biotic and abiotic stresses tolerance and yield [18,19].…”
Section: Genetic Diversity Of Coffea Arabica Lmentioning
confidence: 99%